2022
DOI: 10.1049/cmu2.12416
|View full text |Cite
|
Sign up to set email alerts
|

RIS‐assisted secure UAV communications with resource allocation and cooperative jamming

Abstract: Unmanned aerial vehicles (UAVs) are widely used in wireless communication networks due to their rapid deployment and high mobility. However, in practical scenarios, the existence of obstacles and eavesdroppers will seriously interfere with the communication quality of the UAV network and produce a security risk. Thus, this paper combines reconfigurable intelligent surface (RIS) technology with UAVs to build a secure UAV communication network. Normally, a rotary-wing UAV (labeled as UAV-S) acting as a base stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
(97 reference statements)
0
14
0
Order By: Relevance
“…The limited deployment cost and signal enhancement were simultaneously considered in the network planning problem at the same time. In [18], Guo et al combined RIS technology with unmanned aerial vehicles (UAVs) to build a secure UAV communication network. Average secrecy rate of the communication network was maximised by jointly optimising the flight trajectory, transmit power of the rotary-wing UAV and friendly UAV jammer, and phase shifter of the RIS.…”
Section: Literature Review and Background Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The limited deployment cost and signal enhancement were simultaneously considered in the network planning problem at the same time. In [18], Guo et al combined RIS technology with unmanned aerial vehicles (UAVs) to build a secure UAV communication network. Average secrecy rate of the communication network was maximised by jointly optimising the flight trajectory, transmit power of the rotary-wing UAV and friendly UAV jammer, and phase shifter of the RIS.…”
Section: Literature Review and Background Workmentioning
confidence: 99%
“…The limited deployment cost and signal enhancement were simultaneously considered in the network planning problem at the same time. In [18], Guo et al. combined RIS technology with unmanned aerial vehicles (UAVs) to build a secure UAV communication network.…”
Section: Literature Review and Background Workmentioning
confidence: 99%
“…The literature [13] investigated the resource optimization problem of UAV sensing data transmission to mobile devices and studied the energy utility maximization problem by jointly optimizing the trajectory, velocity, and transmit power of the UAV in the system. In the latest research, by combining Reconfigurable Intelligent Surface (RIS) technology with UAVs, a secure UAV communication network can be constructed for relay transmission [14].…”
Section: Introductionmentioning
confidence: 99%
“…Benefiting from the above superiority, IRS has been studied under various wireless system setups. [20][21][22][23][24][25] In particular, extensive research efforts have been devoted to employing IRS for improving the transmission rate of UAV communications and/or safeguarding them from security threats. It showed that by joint design of the UAV trajectory and IRS passive beamforming, the average achievable rate of the system can be significantly improved.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of IRS‐assisted wireless communications lies in that it considerably increases the channel capacity with low power consumption and can be flexibly deployed in the radio environment. Benefiting from the above superiority, IRS has been studied under various wireless system setups 20‐25 . In particular, extensive research efforts have been devoted to employing IRS for improving the transmission rate of UAV communications and/or safeguarding them from security threats.…”
Section: Introductionmentioning
confidence: 99%